2021
DOI: 10.3390/cells10051074
|View full text |Cite
|
Sign up to set email alerts
|

The Route of Early T Cell Development: Crosstalk between Epigenetic and Transcription Factors

Abstract: Hematopoietic multipotent progenitors seed the thymus and then follow consecutive developmental stages until the formation of mature T cells. During this process, phenotypic changes of T cells entail stage-specific transcriptional programs that underlie the dynamic progression towards mature lymphocytes. Lineage-specific transcription factors are key drivers of T cell specification and act in conjunction with epigenetic regulators that have also been elucidated as crucial players in the establishment of regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 193 publications
0
7
0
Order By: Relevance
“…Multiple studies have uncovered the molecular phenomena behind the lineage plasticity of ETPs, and have designated certain genes as barcodes of particular specification programmes in these multipotent cells (Chiara et al, 2021;Hosokawa and Rothenberg, 2021). However, to the best of our knowledge, this study is the first of its kind to delineate the developmental pliability of the neoplastic forms of these multipotent cells, bringing forth new opportunities to subclassify multipotent ETP-ALL samples based on their lineage bias.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have uncovered the molecular phenomena behind the lineage plasticity of ETPs, and have designated certain genes as barcodes of particular specification programmes in these multipotent cells (Chiara et al, 2021;Hosokawa and Rothenberg, 2021). However, to the best of our knowledge, this study is the first of its kind to delineate the developmental pliability of the neoplastic forms of these multipotent cells, bringing forth new opportunities to subclassify multipotent ETP-ALL samples based on their lineage bias.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, CDR2 can be detected in vascular smooth muscle cells of rats and humans [ 33 ]. Interestingly, CD8+cytotoxic T cells will fail to activate T cells expressing CDR2 in response to epithelial cells expressing CDR2 [ 34 ]. Balamurugan et al indicated that the overexpression of the CDR2 gene plays an important role in repressing HIF-1 transactivation activity by interfering with p300 recruitment in their study on solid tumors [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…BCL11B was identified as an important role in T-cell function [ 34 ], and its lower expression is associated with adverse clinical outcomes for patients with myelodysplastic syndrome [ 36 ]. DUSP2 can control the activity of the transcription activator signal transducer and the activator of transcription 3 in its regulation of TH17 differentiation [ 37 ], and can also act as an immune checkpoint in T-cell antitumor immunity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the critical master regulators for T cell commitment in the thymus, TCF1 is the first T cell-specific transcription factor induced and activated by Notch signaling in the successive stage of T lineage specification, and it maintains a high expression level until T cell maturation (11,12). Activated TCF1 positively regulates two major target genes, B cell leukemia/lymphoma 11B (BCL11B) and GATA binding protein 3 (GATA3), to sustain T cell commitment and proliferation (13)(14)(15)(16)(17). Additionally, as pivotal T cell-specific transcription factors, TCF1 and BCL11B also participate in T cell activation and expansion (15,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%